the community service journal - Kurnianingsih, Asih; Permana, Fransisco Toebagus Dias; Syafrizal, Sutan; Yani, Najla Putri (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2023)
ABSTRACT The objective of the Student Work Program (KKM) activity is to enhance the capacity and skills of the Panamping Village community, Bandung sub-district, in managing the cultivation of Tilapia fish. The work program provides an opportunity for students to gain direct experience in the working world, allowing them to apply the theoretical knowledge acquired during their studies in a real working environment. This KKM activity is participated in by members of fish cultivation groups in the village who have a desire to improve their existing businesses. The challenges faced include the lack of knowledge and skills among the community regarding fish cultivation, especially in plastic ponds, and business planning. Additionally, there is a lack of implementation of good fish cultivation technologies, such as feeding practices, pre-stocking seedling management, all of which can affect fish growth. Moreover, there are no alternative fish rearing facilities, while the demand for tilapia fish is quite high. The method employed in this activity involves an approach that engages members of fish cultivation groups within the village. The implementation of the activity includes the direct provision of 2000 tilapia fish fingerlings. The results of this KKM activity have had a positive impact on the village.